The Integration of Spiritual and STEM Education (IS-STEM) in Muhammadiyah Schools: A Systematic Review for Sustainable Learning - S. Sriyanto; Pratik Hari Yuwono; Sella Dwinanda; Sri Mulyani (Universitas Muhammadiyah Purwokerto, 2026)
Twenty-first-century education requires learners not only to achieve academic proficiency but also to be socially, morally, and environmentally responsible. STEM approaches are proven to enhance cognitive skills, yet they often neglect spiritual and value-based dimensions, limiting their contribution to sustainable learning. This study aims to analyze the concept and implementation of Spiritual-STEM (IS-STEM) for sustainable learning, focusing on teachers ’ understanding, classroom practices, and the dual impacts on students ’ cognitive and affective development. A Systematic Literature Review (SLR) was conducted using the PRISMA model. Articles were retrieved from Scopus, Web of Science, ERIC, SpringerLink, MDPI, Taylor & Francis, Wiley Online Library, covering the period 2019-2025. A total of 412 articles were identified, of which 21 met the inclusion criteria and were analyzed using data extraction and thematic synthesis. The review found that IS-STEM served as a bridge between technical competencies and the internalization of spiritual values. Common pedagogical approaches include Project-Based Learning (PjBL), Engineering Design Process (EDP), and Socio-Scientific Issues (SSI). Findings indicate dual benefits: cognitive improvement (conceptual understanding, systems thinking, and problem-solving) and affective development (environmental awareness, social empathy, and moral orientation). Integrating spirituality into STEM strengthens a holistic and sustainable education paradigm. IS-STEM is highly relevant for Muhammadiyah schools and adaptable to global contexts, balancing modern scientific literacy with spiritual development. Further research is recommended to test IS-STEM ’ s effectiveness empirically and to develop valid instruments for evaluating the spiritual dimensions of learning.